A comparison of ASCAT wind measurements and the HIRLAM model over the Baltic Sea - Jekaterina Služenikina; Aarne Männik (Oceanologia)
This paper presents a comparison of the wind data measured by the ASCAT polar-orbiting satellite scatterometer and winds forecast by the numerical weather prediction model HIRLAM in the Baltic Sea region during the stormy season in 2009. Two different resolution models were used in the comparison. Mutual quality and uncertainty characteristics of the measurements and predictions are determined. The results of the study show that the ASCAT wind data are well correlated with the HIRLAM predicted winds, which raises the credibility of both data sources in operational and hindcasting applications over the Baltic Sea. A case of phase error in a HIRLAM forecast of cyclonic activity over the Baltic Sea is discussed.